Spectral measurements with hybrid LMR and SAW platform for dual parameter sensing. Issue 23 (2nd November 2022) - Dominguez, Ismel; del Villar, Ignacio; Corres, Jesús; Lachaud, Jean-Luc; Yang, Yang; Hallil, Hamida; Dejous, Corinne; Matias, Ignacio R.
Abstract : Hybrid platform combining LMR with SAW technologies to characterize a liquid in terms of its refractive index and viscosity, simultaneously. Abstract : Lossy mode resonance (LMR)-based optical sensors change their wavelength upon contact with substances or gases. This allows developing applications to detect the refractive index of the surrounding medium and even the thickness of the biolayers deposited on the waveguide. In the same way, when acoustic sensors are in contact with a liquid, it is possible to determine parameters, especially mechanical ones such as shape of the particle or molecule, mass load, elastic constants and viscosity of the liquid. This work reports the development of a system that combines LMR with surface acoustic wave (SAW) technologies to characterize a liquid in terms of its refractive index and viscosity simultaneously. Conveniently prepared glucose solutions are used for sensor calibration. The refractive index of the solutions ranges from 1.33 to 1.41 and its viscosity ranges from 1.005 mPa·s to 9 mPa·s, respectively. A sensitivity of 332 nm per RIU has been achieved with the optical sensor while the acoustic sensor has shown a sensitivity of −1.5 dB/(mPa·s). This new combinational concept could be expanded to the development of more demanding applications such as chemical sensors or biosensors.